The power of social media influencers: unveiling the impact on consumers’ impulse buying behaviour - Komal Shamim; Muhammad Azam (Humanities & Social Sciences Communications)
Abstract This study investigates the role of communication factors in influencer marketing communication in influencing trust in influencer’s branded posts, subsequently impacting the urge to buy impulsively (UBI). In addition, the study also examines the role of persuasion knowledge as a moderator and product affection as a mediator in the relationship between trust and UBI. The study integrates signalling theory and (SOR) framework to develop a model to be tested through SEM. Results of the data of 481 followers of the influencers unveiled that the credibility of the communication factors plays an essential role in developing trust in influencers ‘posts, which ultimately induces UBI. Product affection mediates the relationship between trust and UBI and people with low levels of persuasion knowledge were found to have more chances of developing UBI. This study provides valuable insights to the markets and advertisers, enabling them to understand the importance of the credibility of the influencer marketing communication factors, which result in favourable consumer attitudinal and behavioural outcomes. Additionally, it addresses the existing knowledge gap concerning the factors that precede trust formation and examines their subsequent influence on UBI.